PjBL-Based E-Comic Fables for Interpretative Reading of Grade IV Students: E-Komik Fabel Berbasis PjBL untuk Pembelajaran Membaca Interpretatif Siswa Kelas IV - Ritonga, Maharani; Hadi, Wisman; Lubis, Wildansyah (Indonesian Journal of Innovation Studies, 2025)
Background: Reading is a fundamental skill crucial for academic success, particularly interpretative reading which involves analyzing implicit meanings, author intent, and emotional nuances in texts. Specific Background: Indonesian students’ literacy rates remain below the OECD average, with most failing to achieve minimum proficiency in reading, as highlighted by PISA 2022. Knowledge Gap: While digital comics and Project Based Learning (PjBL) have individually shown promise, there is limited research on their integration for enhancing interpretative reading in Indonesian elementary contexts. Aim: This study aims to examine the effectiveness of PjBL-based fable e-comics in improving the interpretative reading abilities of Grade IV elementary students. Results: Using a quasi-experimental one group pretest-posttest design, students’ scores improved significantly from a pretest average of 66 to a posttest average of 91, with an N-gain score of 0.71, indicating high effectiveness. Novelty: The study offers a novel instructional model combining e-comics and PjBL to foster interpretative reading—a synergy not previously explored in this context. Implications: Findings suggest that this innovative approach can enhance literacy instruction, offering practical guidance for educators to design engaging, curriculum-aligned digital learning experiences that align with the Merdeka Curriculum and 21st-century competencies.Highlight : Improves Reading Skills: E-comic fables with PjBL significantly enhance interpretive reading ability. High Effectiveness Score: Achieved an N-gain score of 0.71, categorized as high. Suitable for Elementary Students: Tailored for students' characteristics and supports 21st-century learning. Keywords : E-Comic Fables, PjBL, Interpretive Reading, Elementary School, Effectiveness